PERILAKU EKONOMI DALAM BINGKAI ANTARA AL-MUAMALAH AL-MADDIYAH DAN AL-MUAMALAH AL-ADABIYAH - Abdul Khobir (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2009)
There are three main economic activities that every individual has to do with them in his or her life to achieve economic well-being and prosperity. They are; production, distribution and consumption. Those activities concern not only with need fulfillment and profitability, but also involve human behaviour either producers’ behaviour or consumers’ behaviour. The economic men whose behaviour arises from the scarcity of means to achieve given ends, has made people to behave in a way that is in accordance with economic rationality to achieve maximization. However, rationality does not necessarily imply maximization, as the forms of rationality could be selfish and egoistic, it could also be beneficial for one individual but harmful for the society. This is, because the principle of Economics is that every individual is actuated and motivated by self-interest. In an Islamic perspective, people’s behaviour must be in accordance with the Islamic values and norms and to seek the pleasure of God the almighty. This does not mean to ignore the rational behaviour in economy, but that rationality must be in accordance with the Shari’ah and the Islamic values and norms wich in turn will guide them in dealing with economic activities to bring them into economic well-being and prosperity.